Develop and Implementation of Voice Recognition Robotic Car - Nizam Mohd Shah, Hairol; Kamis, Zalina; Fairus Abdollah, Mohd; Shahrieel Mohd Aras, Mohd; Wasbari, Faizil; Mohd Ali, Nursabillilah; Chia Kuan You, Clement; Ismael Rizman, Zairi (International Journal of Engineering and Technology, 2018)
The idea in this paper is to develop a voice recognition system that can recognized five commands to control a robotic car. The focus area is mainly on voice identification and recognition system. The aim of the system was not recognizing sentences but only isolated a word then demonstrates the action on a simple built robotic car. The system allows user to deliver voice commands through a microphone for control the movement of the car. Voice command is sent to computer and the process to compare the signal with signal stored in database using Vector Quantization (VQ) technique. Mel-wrapping filter bank in feature extraction was used to reduce the root mean square amplitude noise amplitude and also improve signal to noise ratio. Result showed that the robotic car can be controlled by 5 basic voice command which is stop, forward, reverse, turn left and turn right by integrating source code in MATLAB with Arduino UNO microcontroller.Â Â